Die Verordnungen (EG) Nr. 805/2004, (EG) Nr. 1896/2006 und (EG) Nr. 861/2007 und deren Umsetzung in das österreichische Recht - Zangl, Sylvia (LeXonomica, 2021)
Regulations (EC) no 805/2004, (EC) no 1896/2006 and (EC) no 861/2007 and their implementation in Austrian law. The European order for payment procedure and the European small claims procedure are currently an alternative to the existing national procedures available in the Member States. This means that the plaintiff can choose between several types of proceeding. He can begin either the European order for payment procedure or – if the value of dispute without interest, costs and expenses does not exceed 2.000 EUR – the European small claims procedure. On the other hand he can choose between existing variants of proceedings under the national law. For the procedures according to the European Payment Order Regulation and the European Small Claims Regulation are in Austria – regarding the provisions of the §§ 252 and 548 ZPO – in principle subsidiarly applicable rules of the ZPO. If the plaintiff chooses the autonomous Austrian procedure and the requirements of the § 244 ZPO are met, the court must issue an Austrian order for payment. If the defendant does not (in time) file an opposition against the Austrian order for payment, it arises in res iudicata, becomes enforceable and can be certified as an European Enforcement Order, if the requirements of the European Enforcement Order Regulation for Uncontested Claims are met. Uredbe (ES) št. 805/2004, (ES) št. 1896/2006 in (ES) št. 861/2007 ter njihova implementacija v avstrijskem pravu. Evropski plačilni nalog in evropski postopek v sporih majhne vrednosti sta v državah članicah EU alternativa k obstoječim nacionalnim postopkom za pridobitev izvršilnega naslova, tako da tožnik izbira med več vrstami postopkov. Po eni strani sta mu na voljo evropski postopek za izdajo plačilnega naloga in evropski postopek v sporih majhne vrednosti (slednji le v primeru, da vrednost spora brez obresti in stroškov ne presega 2.000 EUR), po drugi strani pa lahko izbere katero od nacionalnih različic civilnega postopka. Za evropska postopka se v Avstriji poleg izvedbenih določb §§ 252 in 548 ZPO načeloma subsidiarno uporabijo določbe avstrijskega ZPO. če se tožnik odloči za postopek po avstrijskem nacionalnem pravu, mora sodišče, če so podane predpostavke iz § 244 ZPO, obligatorno izdati avstrijski plačilni nalog. če tožena stranka ne vloži (pravočasnega) ugovora, postane avstrijski plačilni nalog pravnomočen in izvršljiv ter se lahko potrdi kot evropski izvršilni naslov, če so izpolnjene predpostavke po Uredbi 805/2004 o evropskem izvršilnem naslovu za nesporne zahtevke.